Effect of culture conditions on nitrogen-fixing activity of bacteria isolated from cassava cultivated soils of Vietnam - Cuong, Pham Viet; Hoa, Nguyen Phuong (Academia Journal of Biology, 2021)
The bacteria capable of fixing atmospheric nitrogen were isolated from cassava cultivated soils of Vietnam. The potential isolates were identified by analyzing the 16S rRNA gene and by morphological, biochemical, cultural characteristics. The selected isolates were assigned to the species Bacillus sp. DQT2 M17, Bacillus subtilis DTAN6 M17, and Bacillus megaterium DSHB I8. The effect of culture conditions on the nitrogen-fixing activity of three selected isolates were studied and the obtained results showed that the highest amount of accumulated ammonia was detected after 6 days of incubation at 35 oC, pH 7.0 with sucrose as a carbon source. The selected strains could be exploited as inoculants for microbial fertilizer production.